The utilization of Fermented Azolla flour (Azolla sp) meal using cow rumen Liquor In the diets on growth performance of this Catfish Fry (Pangasius hypophthalmus) - Malik Malik; Indra Suharman; Adelina Adelina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The research was conducted for 56 days from August to October 2017. The aim of this research was to know the optimum amount of fermented Azolla flour (Azolla sp) meal using cow rumen liquor in the diets on growth and feed performance of catfish fry. Completely randomized design (CRD) was used in this experiment, with one factor, five level treatments and three replications. The fish used in this research with size 3-5 cm in 2-4g of weight. Fish were reared in 1 m3 cages with stocking density 25 fish. Feeding trial were replacing soybean meal with fermented azolla meal applied to P1 (0%), P2 (10%), P3 (15%), P4 (20%), and P5 (25%) for 35% of protein content. The result showed that fermentedazolla leaf meal gave significant effect (P>0,05) on growth, feed efficiency and feed digestibility of catfish fingerling. Replacement 25% of azolla meal  fermented is the best response, produce the highest specific growth rate 3,27%, feed efficiency 40,77% and feed digestibility 73,12%. Key word : Azolla Meal, Cow Rumen Liquor, Fermentation, Growth, Pangasius hypophthalmus, Soybean Meal